EVALUASI PROGRAM PENGELOLAAN PERTANAHAN NASIONAL - Sapto Budi Santoso, Mr. (Jurnal Ilmiah Administrasi Publik, 2012)
In order to realize land reform in Indonesia, National Land Agency (BPN) conducts IP4T (Land Inventory of Tenure, Ownership, Use and Utilization). This activity is intended as a data base of land areas in Indonesia and synchronization activities of land. During this time the use of data results IP4T activity was less optimal, especially as the synchronization of planning activities to accelerate the legalization of land assets. The purpose of this thesis is: firstly to evaluate the implementation of the Land Inventory of Tenure, Ownership, Use and Utilization (IP4T) program in East Java Province, secondly to analyze the utilization of the IP4Tâs results in the land management planning process in East Java. This research used qualitative method with descriptive approach. The conclusions obtained, Execution / implementation of IP4T in East Java Province, has been running well in quantity has been largely imposed to meet the target over the years, but planning activity from the activity IP4T land in East Java Province, it can be said the less successful as a result of these activities IP4T less fully utilized